Pengaruh Carbopol940 Dan CMC-Na Terhadap Karakteristik, Stabilitas Fisik, Efektivitas, Dan Iritabilitas Ubiquinone – Nanostructured Lipid Carries (NLC) Dalam Hydrogel Sleeping Mask Sebagai Kosmetik Antiaging - Sanky Indrajaya, - (2021)
Ubiquinone is an endogenous antioxidant enzyme found in almost every cell and helps reduce Reactive Oxygen Species (ROS) production, also inhibits lipid peroxidase. Ubiquinone disadvantages are low water solubility, large molecular weight, high lipophicility. This makes ubiquinone need a formulation to increase the effectiveness. This study aim is to compared Ubiquinone-NLC hydrogel sleeping mask (HSM) with different gel base types, Carbopol 940 (F2) and CMC-Na (F3) against Ubiquinone-NLC (F1). Ubiquinone-NLC HSM is made by mixing ubiquinone-NLC and HSM base in 1:1 ratio using 200 rpm Ultraturrax for 10 minutes. The preparation then performed characterization included pH, viscosity, particle size and polydispersity index followed by penetration, effectivity test, physical stability for 45 days. The results of the characterization test are pH F1 = 6.023 ± 0.012, while F2 = 6.039 ± 0.030, and F3 = 6.031 ± 0.015. Viscosity F1 <24.9 cPs, F2 = 232.9 cPs, and F3 = 240.3 cPs. particle size F1 = 119.9 ± 19.71 nm, F2 = 125.4 ± 23.36 nm, and F3 = 128.2 ± 13.24 nm. The polydispersity Index F1 = 0.295 ± 0.01, F2 = 0.329 ± 0.02, and F3 = 0.331 ± 0.01. In-vivo effectiveness test results were carried out. After 4-hour nile-red penetration test showed F2 and F3 had better skin penetration than F1. Collagen density and number of fibroblasts test on the skin of the mice back for 14 days showed F2 and F3 had better results than F1, UV, Control. Irritation test were carried out in vivo. After 24 hours showed that F1, F2, F3 are non-irritating. The physical stability test showed F3 had the best stability in terms of pH, spreadability, particle size, and polydispersity index. Conclusion of this study are different types of gelling agent affect characteristic of ubiquinone-NLC HSM which had better effectivity than ubiquinone-NLC, all of formula are nonirrtitating, and ubiquinone-NLC in HSM CMC-Na had the best stability for 45 days of storage.